Answer:
f(x)=(x-12)^2
Step-by-step explanation:
We know that the function f(x+m) equals to the function f(x) translated 'm' times to the left. Therefore, to translate the function f(x) = x^2 twelve units to the right, we have to:
f(x-12) = (x-12)^2
Therefore, the new function is: f(x)=(x-12)^2
Answer:
(3, -9)
General Formulas and Concepts:
<u>Pre-Algebra</u>
- Order of Operations: BPEMDAS
- Equality Properties
<u>Algebra I</u>
- Solving systems of equations using substitution/elimination
- Solving systems of equations by graphing
Step-by-step explanation:
<u>Step 1: Define systems</u>
-5x - 3y = 12
y = x - 12
<u>Step 2: Solve for </u><em><u>x</u></em>
<em>Substitution</em>
- Substitute in <em>y</em>: -5x - 3(x - 12) = 12
- Distribute -3: -5x - 3x + 36 = 12
- Combine like terms: -8x + 36 = 12
- Isolate <em>x</em> term: -8x = -24
- Isolate <em>x</em>: x = 3
<u>Step 3: Solve for </u><em><u>y</u></em>
- Define original equation: y = x - 12
- Substitute in <em>x</em>: y = 3 - 12
- Subtract: y = -9
<u>Step 4: Graph systems</u>
<em>Check the solution set.</em>
The answer is 71°.
x = angle
3x = 90 - x - 14
4x - 76
x = 19°
90 - x = 71°
Answer:
an=an-1
Step-by-step explanation:
as it doesnt have -6 +3n
X divided by two is 5
So you multiply 5 and 2 to get 10. Therefore x equals 10